Determination of Different Parameters and Their Corelation with Sleep Disorder Breathing and Assessing the Viability of a Measuring Scale in Children - Sharvani, Kuruva; Ram, Kandregula Chaitanya; Balakrishna, Kandarpa; Bharathi, Lavudu; Navya, Matta; Eluri, Bhagya Lakshmi (Journal of Neonatal Surgery, 2025)
Aim: The aim of the article is to identify viable and functional extra oral and intra oral features which might be associated with increased risk of sleep disturbances in paediatric patients and to develop a functional air way screening tool for easy diagnosis of paediatric sleep disordered breathing Methods: A cross-sectional stud was conducted among 750 children aged 5-10 years Clinical examination which includes functional, extraoral, intraoral soft tissue, and intraoral hard tissues similar to SDSC and fairest scale. The present study includes few additional factors Like presence of day symptoms and night symptoms which were also recorded Results: Include that there is association with the above findings and sleep disorder breathing in children Conclusion: The Pediatric Sleep Breathing Assessment Scale (PSBA) Is Reliable and Provides a valuable information about behaviour patterns, sleep patterns of children, quality of life of children, symptoms of children who are suffering from sleep disorder breathing.